Submerged jet impingement for immersion cooling of high performance servers - Raphael Luke Nesaraj Ravindran Rufus (Nanyang Technological University, 2020)
Advancement in technology has led to major developments in the field of servers and central processing units. Traditionally they were large and bulky equipment, however, in recent times these serves are manufactured in sizes small as our palms. These processors can be found across many industries ranging from aerospace to data centres to automotive all over the world. Though there are many advantages in the reduction of size there comes certain disadvantages too. One of which that requires great concern from researchers is to curb the increase in heat flux due produced by these servers. There is an increase in demand for these high-performance servers and hence greater efficient technology and methods are required. Thus the author has built a two-phase liquid immersion cooling system for the high-performance to research on methods to improve cooling processes. Two promising methods to achieve high heat transfer performance is through nucleate pool boiling and submerged jet impingement cooling technique. Ultra-Pure Water has been used as the coolant. The copper heating test piece simulates the high-performance servers. The liquid level sensor, thermal sensor, flowmeter, and pressure sensor were applied into the system to monitor the system working conditions. Saturated pool boiling experiments at atmospheric conditions were conducted on the eight surfaces till Critical Heat Flux (CHF) was met. The two microgrooves and one plain surface with Roughness Average (Ra) of 0.06μm was further experimented on by in cooperating submerged jet impingement cooling with Reynolds number of 12000. The submerged jet impingement cooling experiment confirms that the average heat transfer coefficient for plain, microgroove deep and microgroove shallow surface was increased by 24%, 43% and 69% respectively as compared to pool boiling. The CHF was also further enhanced in comparison to pool boiling. However, the main focus of this report is to convey experimental and theoretical studies on immersion cooling and how it could be enhanced through submerged jet impingement. Additional study on bubble dynamics and active nucleation site would be extremely anticipated to detect the most underlying element that influences the heat transfer performance. For future studies, submerged jet impingement array could be created with thermocouple placed in an orientation to capture three-dimensional heat transfer through heating element.